2019
DOI: 10.1093/femsec/fiz174
|View full text |Cite
|
Sign up to set email alerts
|

The patterns of nitrogen fixation in haloalkaliphilic phototrophic communities of Kulunda Steppe soda lakes (Altai, Russia)

Abstract: Nitrogen fixation (NF) of phototrophic communities was studied in a number of soda lakes with a wide range of salinity (25–400 g/l) located in Kulunda Steppe (Altai, Russia) during several summer seasons (2011–2016). The phototrophic communities were represented by the algal-bacterial Ctenocladus communities or cyanobacterial biofilms dominated by heterocystous and non-heterocystous cyanobacteria and purple sulfur bacteria Ectothiorhodospira sp. (up to 210 g/l) and endoevaporitic Euhalothece communities domina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…Based on protein annotations, the GSL Euhalothece population is also likely capable of fermenting pyruvate into formate, lactate, and acetate and can convert dinitrogen (N 2 ) to ammonia via molybdenum (Mo)-dependent nitrogenase. This characteristic is consistent with recent reports of N 2 fixation in this genus (35) and indicates that Euhalothece likely supplies both fixed carbon and nitrogen for secondary consumers in GSL. As such, Euhalothece likely represents a keystone species in the GSL mat community and the broader ecosystem (23,36).…”
Section: Resultssupporting
confidence: 92%
“…Based on protein annotations, the GSL Euhalothece population is also likely capable of fermenting pyruvate into formate, lactate, and acetate and can convert dinitrogen (N 2 ) to ammonia via molybdenum (Mo)-dependent nitrogenase. This characteristic is consistent with recent reports of N 2 fixation in this genus (35) and indicates that Euhalothece likely supplies both fixed carbon and nitrogen for secondary consumers in GSL. As such, Euhalothece likely represents a keystone species in the GSL mat community and the broader ecosystem (23,36).…”
Section: Resultssupporting
confidence: 92%
“…Recent microbiological studies of Kulunda steppe soda lakes have led to the isolation of several new taxa of alkaliphilic prokaryotes [18–27] and to the characterization of various microbial processes taking place in these habitats [28–39]. In particular, it was shown that the dead biomass of the primary producers could serve as a source of proteins and peptides for numerous proteolytic bacteria, including members of the phylum Firmicutes Proteinivorax tanatarense [40, 41] and Proteinivorax hydrogeniformans [42] or Candidatus ‘Cyclonatronum proteinivorum’ of the phylum Balneolaeota [43].…”
Section: Full-textmentioning
confidence: 99%
“…High salt concentrations and alkaline pH values in natural habitats yield the emergence of specific communities of prokaryotic and eukaryotic organisms, with a pronounced dominance of a small number of adapted species [1][2][3][4][5][6]. Every part of the community plays its own role and is strongly connected to the other parts [7][8][9].…”
Section: Introductionmentioning
confidence: 99%